NUTRITIONAL AND ANTIOXIDANT POTENTIAL OF LYOPHILIZED WHEAT GRASS JUICE AND SHOOT POWDERS - N.M. JABEEN*, POOJA YADAV, MAHADEVA NAIKA, MALLESHA; N. DEVANNA (The Journal of Research ANGRAU, 2020)
Young wheatgrass is rich in vitamins, minerals, chlorophyll, bioactive compounds, and fiber. In this study, phytochemicals, proximate analysis, amino acids, individual polyphenols, minerals, and antioxidants of lyophilized wheatgrass juice powder and shoot powder were estimated. Both the samples (juice and shoot powders) showed the presence of phytochemicals such as alkaloids, tannins, cardio-glycosides, coumarins, flavonoids, carbohydrates, etc. Further more, HPLC analysis of individual polyphenols showed that the juice powder had significantly higher (P <0.05%) quercitin, sinnapic acid, chlorophyll, and essential amino acids like valine, threonine. Wheat grass juice powder have shown significantly higher (p<0.05%) Fe and Zn than shoot powder. Juice powder had significantly more (P<0.05) total polyphenols (15.20±1.0 mg/g), total flavonoids (6.27±0.68 mg/g) than shoot powder, and DPPH activity with IC50 1.48±0.15 mg/g. This study highlights the nutritional benefits of wheatgrass juice powder as lyophilization could reduce losses of nutrients and antioxidants. These findings confirm that lyophilized wheatgrass juice powder is medicinally important with bioactive compounds, antioxidant capacity, and have significant potential to incorporate in functional food products those can be used to enhance the health benefits of consumer.